2018
DOI: 10.1371/journal.pgen.1007273
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene induced plant stress tolerance by Enterobacter sp. SA187 is mediated by 2‐keto‐4‐methylthiobutyric acid production

Abstract: Several plant species require microbial associations for survival under different biotic and abiotic stresses. In this study, we show that Enterobacter sp. SA187, a desert plant endophytic bacterium, enhances yield of the crop plant alfalfa under field conditions as well as growth of the model plant Arabidopsis thaliana in vitro, revealing a high potential of SA187 as a biological solution for improving crop production. Studying the SA187 interaction with Arabidopsis, we uncovered a number of mechanisms relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
119
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(125 citation statements)
references
References 88 publications
2
119
0
Order By: Relevance
“…root system architecture by reducing primary root growth (shorter primary root length) and increasing the lateral root density of plants under salinity stress using both inoculation settings. Previously isolated endophytes of the Enterobacteriaceae family (SA187, JZ29) also exhibited a similar pattern of growth promotion with higher LRDs compared to mock plants (de Zélicourt et al, 2018;Eida et al, 2019). The ability of JZ38 to promote growth in the contactless set-up suggested that volatile compounds are emitted by JZ38 which help plants to grow under saline conditions.…”
Section: Jz38 Promotes Arabidopsis Growth Under Salinity Stressmentioning
confidence: 75%
See 3 more Smart Citations
“…root system architecture by reducing primary root growth (shorter primary root length) and increasing the lateral root density of plants under salinity stress using both inoculation settings. Previously isolated endophytes of the Enterobacteriaceae family (SA187, JZ29) also exhibited a similar pattern of growth promotion with higher LRDs compared to mock plants (de Zélicourt et al, 2018;Eida et al, 2019). The ability of JZ38 to promote growth in the contactless set-up suggested that volatile compounds are emitted by JZ38 which help plants to grow under saline conditions.…”
Section: Jz38 Promotes Arabidopsis Growth Under Salinity Stressmentioning
confidence: 75%
“…Five-day old seedlings (∼1.0-1.5 cm in root length) were then gently transferred to fresh 1/2MS agar plates supplemented with 100 mM NaCl as a salt stress (five seedlings/plate). For contact (in-plate) assays, seeds were sown on 1/2MS plates containing JZ38 (2 × 10 5 CFU/mL) prior to stratification (100 µL of pure LB was added as a control) (de Zélicourt et al, 2018). For contactless assays, sterile 15 mL Falcon tube caps (VWR) were placed at the bottom of each square Petri dish before pouring the 1/2MS media.…”
Section: Plant Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…However, acclimatizing plants under field conditions is not 73 always feasible. The use of endophytes and other rhizobacteria (known as plant growth 74 promoting bacteria, PGPB) as a reliable and feasible method to promote plant growth under 75 abiotic stress conditions such as drought, salinity, metal toxicity, and elevated temperatures 76 was suggested (de Zélicourt et al, 2018;Numan et al, 2018). The interaction between plants and 77 endophytes leads to enhanced plant growth under heat stress conditions (Marquez et al, 2007).…”
Section: Introductionmentioning
confidence: 99%